2012
DOI: 10.1136/amiajnl-2011-000307
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and evaluation of web-accessible tools for management of diabetes and related cardiovascular risk factors by patients and healthcare providers

Abstract: ObjectiveTo identify and evaluate the effectiveness, clinical usefulness, sustainability, and usability of web-compatible diabetes-related tools.Data sourcesMedline, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, world wide web.Study selectionStudies were included if they described an electronic audiovisual tool used as a means to educate patients, care givers, or clinicians about diabetes management and assessed a psychological, behavioral, or clinical outcome.Data extractionStudy abstraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 77 publications
(188 reference statements)
2
57
0
Order By: Relevance
“…A majority of the studies focused on the glucose monitoring process-such as allowing patients to upload their data so that healthcare providers may adjust their medication and dosage. 12,13 Technology interventions were observed to be effective and versatile in facilitating the management of the condition 14,15 and support the resultant changes in lifestyle. 16 With increasing interest in the use of games for health care, the objective of this study is to review the literature that focuses on the use of videogames, gamification methods, and VEs for day-to-day self-management of people with diabetes.…”
Section: Introductionmentioning
confidence: 95%
“…A majority of the studies focused on the glucose monitoring process-such as allowing patients to upload their data so that healthcare providers may adjust their medication and dosage. 12,13 Technology interventions were observed to be effective and versatile in facilitating the management of the condition 14,15 and support the resultant changes in lifestyle. 16 With increasing interest in the use of games for health care, the objective of this study is to review the literature that focuses on the use of videogames, gamification methods, and VEs for day-to-day self-management of people with diabetes.…”
Section: Introductionmentioning
confidence: 95%
“…One of the most important cases in intervention implementation is usability testing [53] but this is often neglected, with up to 60% of diabetes-related websites having a minimum of 4 usability errors. So it can be said that the gold standard for intervention development should be represented to obtain high intervention effectiveness [54]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of web-accessible tools for management of diabetes [5] found that few web-based tools met all their health outcome criteria for clinical effectiveness, clinical usefulness, sustainability, and usability. They also found that greater interactivity resulted in better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, current implementations suffer from limited effectiveness and usability errors, and consequently have high user attrition rate [5]. Our App uses open source tools for software development, semantic web and Health IT [6][7][8], so other researchers and entrepreneurs can build on our work and develop their own creative extensions.…”
Section: Introductionmentioning
confidence: 99%